2016
DOI: 10.1590/1980-5373-mr-2015-0411
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the Synthesis, Optical and Electrical Properties of TiO2 Thin Films by Chemical Bath Deposition (CBD) method

Abstract: Titanium dioxide (TiO 2 ) thin films were prepared by Chemical Bath Deposition (CBD) method. The X-ray diffraction (XRD) analysis was used to examine the structure and to determine the crystallite size of TiO 2 thin film. The surface morphology of the film was studied using Scanning Electron Microscopy (SEM).The optical properties were studied using the UV-Visible and photoluminescence (PL) spectrum. Optical constants such as band gap, refractive index, extinction coefficient and electric susceptibility were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(28 citation statements)
references
References 31 publications
3
25
0
Order By: Relevance
“…As Figure a shows, the diffraction peak at 2θ (degrees) of 25.35 was indexed as (101) planes corresponding to that of the tetragonal wurtzite structure of TiO 2 . [ 20 ] In the case of Al‐doped TiO 2 films, the diffraction peak (101) shifted to a higher angle at 2θ (degrees) of 25.45 as compared to pristine TiO 2 film. [ 21 ] From these values, we calculated the average grain size (D) and d‐spacing (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…As Figure a shows, the diffraction peak at 2θ (degrees) of 25.35 was indexed as (101) planes corresponding to that of the tetragonal wurtzite structure of TiO 2 . [ 20 ] In the case of Al‐doped TiO 2 films, the diffraction peak (101) shifted to a higher angle at 2θ (degrees) of 25.45 as compared to pristine TiO 2 film. [ 21 ] From these values, we calculated the average grain size (D) and d‐spacing (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…Nano rosette TiO2 was synthesized through deposition on top of a fluorine-doped tin oxide (FTO, 30 Ω/cm 2 ) glass substrate via a hydrothermal method similar to the previously reported procedure used by Govindasamy et al (2016) with a slight modification. In a typical synthesis, distilled water was mixed with hydrochloric acid at a fixed volume ratio of 1:1 to reach a total volume of 40 mL in a beaker glass.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the 3D nano-flower hierarchical structures of TiO2 have been proven to enhance its photocatalytic properties (Zhou et al, 2013). Xiao et al (2017) and Govindasamy et al (2016) have reported that the use of a combination of compact TiO2 layers with the growth of TiO2 nanorods as an electron transporting layer has improved the performance of perovskite solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been used to prepare TiO 2 other metal oxide nanostructure films, including chemical vapor deposition (CVD) [1], pulsed laser deposition [2], reactive sputtering [3], chemical bath deposition (CBD) [4] [5] and sol-gel spin coating [6] [7]. The sol-gel spin coating has emerged as one of the new commercially viable nano-TiO 2 fabrication methodologies as this method produces samples with a uniform synthetic strategy needed for high-efficient UV-Vis optical response.…”
Section: Introductionmentioning
confidence: 99%